2018
DOI: 10.1038/s41598-018-22093-3
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of the spliced leader trans-splicing mechanism in Schistosoma mansoni

Abstract: Spliced leader dependent trans-splicing (SLTS) has been described as an important RNA regulatory process that occurs in different organisms, including the trematode Schistosoma mansoni. We identified more than seven thousand putative SLTS sites in the parasite, comprising genes with a wide spectrum of functional classes, which underlines the SLTS as a ubiquitous mechanism in the parasite. Also, SLTS gene expression levels span several orders of magnitude, showing that SLTS frequency is not determined by the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 57 publications
5
28
0
Order By: Relevance
“…This pathway also seems to act in the regulation of alternative splicing in response to extracellular stimuli, promoting changes in splicing patterns (Pelisch et al, 2005). Moreover, Schistosoma presents trans-splicing, which is a peculiar mechanism that shares the proteins from the spliceosome, could affect up to 58% of transcripts in the cercarial stage (Boroni et al, 2018). It has been suggested as a target for parasite impairment and would be affected by the alterations detected in categories related to RNA splicing (Mourão et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway also seems to act in the regulation of alternative splicing in response to extracellular stimuli, promoting changes in splicing patterns (Pelisch et al, 2005). Moreover, Schistosoma presents trans-splicing, which is a peculiar mechanism that shares the proteins from the spliceosome, could affect up to 58% of transcripts in the cercarial stage (Boroni et al, 2018). It has been suggested as a target for parasite impairment and would be affected by the alterations detected in categories related to RNA splicing (Mourão et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…If desired, operon prediction can take intercistronic distances into account, either via a user-supplied distance cutoff or via an automatic K-means clustering method that splits the genome-wide distribution of intercistronic distances into two groups, corresponding to tight gene clusters (potential operons) and non-operonic genes. As such, by manually specifying SL1/SL2-type SLs, SL2:SL1 ratio cutoff, upstream gene designation and intercistronic distance cutoff, a large gamut of relationships between SLs and operonic genes can be explored, even in situations where no subfunctionalisation of SLs for operon resolution exists, for example in kinetoplastids or tunicates [20][21][22].…”
Section: Sloppr: Spliced Leader-informed Operon Prediction From Rna-seqmentioning
confidence: 99%
“…The same SL2-type specialisation of some SLs for resolving downstream genes in operons has been reported in other nematodes [14][15][16][17][18][19], but is not seen in other eukaryotic groups. For example, platyhelminth Schistosoma mansoni and the tunicates Ciona intestinalis and Oikopleura dioica each possess only a single SL, which is used to resolve polycistronic RNAs but is also added to monocistronic transcripts [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…At least in some cases, it has been shown that it can also play an important role generating different isoforms by facultative SL trans-splicing (e.g. [10]) or alternative SL trans-splicing acceptor sites [11]. The number of classes of SLs (i.e., Spliced Leaders with a distinct sequence) and the number of copies in each genome varies among different organisms, and at least in some cases, there is evidence of specialization.…”
mentioning
confidence: 99%
“…For example, "SL Trapping" [27] or "SL-seq" [28], both modified Next Generation Sequencing (NGS) protocols, allow an enriched sequencing of SL trans-spliced transcripts (e.g. [11]). Other approaches exist, but they either focus on identifying trans-splicing acceptor sites on the coding genes (e.g.…”
mentioning
confidence: 99%